On ??Statistical Convergence of Order ? of Sequences of Function - Aral, Nazlım Deniz; Kandemir, Hacer Şengül; Et, Mikail (American Institute of Physics Inc., 2022)
In this study, by using definition of ?-statistical convergence which defined by Çakallı [5] we introduce the concepts of pointwise w?? (f)-summability, pointwise ?-statistical convergence of order ? and uniform ?-statistical convergence of order ? sequences of real-valued functions. Also, we give some inclusion relations between these concepts. © 2022 American Institute of Physics Inc.. All rights reserved.
5th International Conference of Mathematical Sciences, ICMS 2021 -- 23 June 2021 through 27 June 2021 -- Istanbul -- 184127
Keywords: Cesàro summability; Sequences of function; Statistical convergence